Bibliometric Analysis and Prisma: Sustainable Consumption in Economics - Arkanudin Rizki Permono; Muhammad Imam Wicaksono; Aris Hanafiah (Riviera Publishing, 2026)
able consumption has become a strategic issue in economic research due to the increasing urgency of environmental crises, climate change, and shifts in consumer behavior toward more responsible consumption patterns. These complex challenges highlight the need for a comprehensive scientific mapping to understand research trends, allocation patterns, and conceptual developments in this field. This study aims to examine research trends, allocation patterns, and implications related to sustainable consumption in economics in order to identify future research directions and strengthen theoretical contributions. The study applies a Systematic Literature Review (SLR) approach based on the PRISMA framework to systematically identify and select relevant studies. A total of 174 articles indexed in the Scopus database were analyzed. Bibliometric analysis was conducted using VOSviewer to map global academic collaboration networks, research clusters, and thematic developments. The findings indicate that sustainable consumption continues to hold strong research significance and future relevance, driven by the urgency of environmental crises and evolving consumer behavior. The global academic collaboration map is dominated by European countries, with a primary focus on developing quantitatively measurable evaluation models. The literature also emphasizes the need for standardizing comprehensive evaluation metrics, such as Life Cycle Assessment (LCA) and Material Flow Analysis (MFA). Theoretically, future research should prioritize the standardization and integration of evaluation metrics to strengthen the validity and comparability of sustainable consumption measurements. Practically, the implementation of a circular economy system requires technological innovation and cross-sector collaboration to bridge the gap between consumer attitudes and actual sustainable consumption behavior